Analysis of world biathlon leaders' participation in biathlon World Cup (on example of women's biathlon) - R.A. Zubrilov; O.M. Pidgrushna (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: optimization of elite female biathlons' training, considering modern structure of international competitions. Material: we analyzed materials of three recent IBU Congresses and more than 3300 protocols of competitions of World cup stages, world championships, winter Olympic Games (women, sport seasons from 2005 to 2015). Results: it was found that, when preparing for winter Olympic Games 63.9% of sportsmen - prize winners missed 13.6% of stages of World Cup, when preparing for world championships 47.2% of prize-winners missed 9.5% of stages. Before the main start of the season in Europe prize winners missed in conditions of plain: 42.1% - 7.9% of World Cup stages; in midlands conditions 61.9% - 13.9%; in competitions with preliminary trans-meridian travel 54.2% of prize-winners missed 13.1% of stages. Conclusions: most of medals are won at world championships and Olympic Games by sportswomen, who are in top-10 of World Cup. The World Cup calendar of events forces sportsmen to miss some stages of World Cup, when they prepare to main start of season. Attitude of world biathlon leaders to missing of World Cup stages before main start of season depends on main character of main start of season. With it main condition for taking decision about missing of World Cup stages is rank of competitions and geographical characteristics of places of competitions.